2023
DOI: 10.1039/d2fo03776a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of umami peptides based on virtual screening and molecular docking from Atlantic cod (Gadus morhua)

Abstract: Umami peptides have currently become the research focus in the food umami science field and the key direction for umami agent development. This is because umami peptides have good processing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…To further verify the effectiveness and robustness of the model, we collected 91 wet-experiment verified umami peptide sequences reported in the latest literature [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. These empirical umami peptide sequences constituted the dataset UMP-VERIFIED, which was then used to test state-of-the-art methods, including UMPred-FRL [ 11 ] and iUP-BERT [ 12 ] for comparison to iUmami-DRLF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further verify the effectiveness and robustness of the model, we collected 91 wet-experiment verified umami peptide sequences reported in the latest literature [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. These empirical umami peptide sequences constituted the dataset UMP-VERIFIED, which was then used to test state-of-the-art methods, including UMPred-FRL [ 11 ] and iUP-BERT [ 12 ] for comparison to iUmami-DRLF.…”
Section: Resultsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Figures S1–S3: iUmami-DRLF web server interface; Table S1: Results of 10-fold cross-validation and independent testing about SMOTE; Table S2: Prediction-probability results of the three models and 91 wet-experiment validated umami peptide sequences [ 5 , 6 , 11 , 56 , 59 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ].…”
mentioning
confidence: 99%
“…Toxicity and water solubility of peptides are important issues in peptide development because they are critical for their applicability in future functional food and drug development. 33 In this study, Innovagen and ADMETlab 2.0 servers were used to predict the water solubility and toxicity of the identified peptides. The predicted results showed that none of these peptides were toxic and 12 of them had good water solubility (Table 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, it is essential to find a safer alternative to MSG. Umami peptides are naturally present in a variety of foods and have great nutritional value, which conforms to the development trend of “natural, nutritious, and safe” food . Therefore, umami peptides have become a research hotspot in the field of food umami in recent years .…”
Section: Introductionmentioning
confidence: 89%
“…The active residues mainly included His145, Ser146, Ser147, Glu148, Gly168, Ala169, Ser170, Met171, Val187, Try218, Ser276, Val277, Glu301, Ala302, Try303, Leu304, Gln356, and His387. Several key residues have been reported to exist in VFTD, including Glu301, Ala302, Ser146, His145, and His387, where umami peptides from Trachinotus ovatus, Chouguiyu, and Atlantic cod (Gadus morhua) were derived. These amino residues are all depicted in Figure G.…”
Section: Resultsmentioning
confidence: 99%